Prevalence and Demographic of Spontaneous Intracerebral Hemorrhage Cases In Haji Adam Malik Hospital From 2018-2019 - Irsyad, Muhammad Ari; Hutagalung, Tommy Rizky; Farhan, luthfi; Tala, Muhammad Ihsan Zulkarnain (Talenta Universitas Sumatera Utara, 2020)
Introduction: Spontaneous intracerebral hemorrhage (ICH) represents as cerebral parenchymal bleeding that may also extend into ventricular (IVH). ICH, as a stroke subtype, is associated with poor neurological outcome as well as high mortality in 40% cases. Hypertension is the main and the most common risk factor in the development of ICH, particularly in the basal ganglia, thalamus, pons and deep cerebellar white matter. Hypertensive ICH in these localizations are particularly common in patients with chronic hypertension and they are not in compliance with blood pressure management. Other risk factor such as smoking and diabetes meilitus. Case Report: This retrospective study reviewed patient who were diagnosed with spontaneous intracerebral hemorrhage from January 2018 until December 2019 at the Haji Adam Malik General Hospital Medan,Indonesia. The patient’s demographic data and number of cases are collected. There were 163 cases of pure spontaneous ICH and 159 cases of Spontaneous ICH with IVH were among the total cases of ICH from 2018 to 2019. Discussion: Based on data at the Haji Adam Malik General Hospital Medan from 2018 to 2019,there are differences in the number of men and women proportion in the incident of pure ICH , for men who are 110 people around 67% while in women it is 53 people or about 32%. The incidence also higher in diabetes meilitus and smoking patient. Conclusion: We reported 163 cases of pure ICH and 159 cases of ICH with IVH. Based on demographic examination, male are dominant about 67% of total cases. Based on the biggest risk factors in patients with spontaneous ICH are hypertension, in the case of spontaneous ICH with IVH the biggest risk factor was smoking.